2005
DOI: 10.1200/jco.2005.08.119
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Decreases the Interstitial Fluid Pressure and Improves Oxygenation in Breast Cancers in Patients Treated With Neoadjuvant Chemotherapy: Clinical Implications

Abstract: Paclitaxel significantly decreased the IFP and increased the pO(2), whereas doxorubicin did not cause any significant changes. Tumor physiology could potentially be used to optimize the sequence of neoadjuvant CT in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
125
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(129 citation statements)
references
References 24 publications
3
125
1
Order By: Relevance
“…Furthermore, tumour hypoxia is associated with poor overall and disease-free survival, greater disease recurrence and less locoregional control in head and neck cancer, cervical carcinoma and soft-tissue sarcomas (Brizel et al, 1999;Birner et al, 2000;Bachtiary et al, 2003;Harrison and Blackwell, 2004). In addition, a statistically significant relationship between IFP and tumour oxygenation has been demonstrated in breast cancer patients (Taghian et al, 2005). In an animal model of metastatic prostate cancer, animals treated with Imatinib plus paclitaxel had significantly smaller tumours, and fewer bone and lymph node metastasis than mice treated with placebo or paclitaxel alone (Uehara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tumour hypoxia is associated with poor overall and disease-free survival, greater disease recurrence and less locoregional control in head and neck cancer, cervical carcinoma and soft-tissue sarcomas (Brizel et al, 1999;Birner et al, 2000;Bachtiary et al, 2003;Harrison and Blackwell, 2004). In addition, a statistically significant relationship between IFP and tumour oxygenation has been demonstrated in breast cancer patients (Taghian et al, 2005). In an animal model of metastatic prostate cancer, animals treated with Imatinib plus paclitaxel had significantly smaller tumours, and fewer bone and lymph node metastasis than mice treated with placebo or paclitaxel alone (Uehara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of IFP and pO 2 measurements in patients with cervical cancer demonstrate that IFP is a stronger predictor than hypoxia for pelvic recurrence and disease-free survival (Milosevic et al, 2004). Although the relationship between IFP and pO 2 is not fully understood, hypoxia is believed to be associated with an increased IFP in solid tumours (Taghian et al, 2005).…”
mentioning
confidence: 99%
“…Cancer cells may experience physical forces in a variety of settings. Cancers growing rapidly against a constraining stroma may exhibit increased interstitial pressures (15,16), whereas metastasizing tumor cells experience pressure and shear during passage through the lymphatics or vasculature. Perioperatively, cancer cells are commonly shed from tumors into the surgical site or the venous circulation during procedures, and the presence of free tumor cells on the outside of the surgical specimen correlates adversely with prognosis for colon cancers (17).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, IFP was used as a prognostic factor and this showed that it was the single best indicator of survival for patients with cancer of the cervix where a high IFP was associated with a poor prognosis (25). More recently, it has been shown that Avastin, the vascular endothelial growth factor A antibody, and paclitaxel could lower the IFP of renal and breast tumors, respectively (26,27). A demonstration of a correlation between changes in tumor growth and IFP in the same tumor would suggest that IFP could be used as a surrogate biomarker of response.…”
mentioning
confidence: 99%